2011
DOI: 10.1007/s00535-011-0465-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria for IgG4-related sclerosing cholangitis based on cholangiographic classification

Abstract: Diagnostic criteria for IgG4-SC based on cholangiographic classification are useful for distinguishing it from PCa, PSC, and CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
114
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 126 publications
(120 citation statements)
references
References 20 publications
2
114
1
3
Order By: Relevance
“…Nakazawa et al considered biliary stricture limited to the intra-pancreatic area as IgG4-SC. 7,8 Naitoh et al reported that lower bile duct strictures appeared as marked wall thickening in 93% of patients, and as extrinsic compression in 7% of patients, revealing lower bile duct stricture caused mostly by bile duct wall thickening. 12 Other 14 studies also support that lower bile duct stricture in AIP is due to inflammatory processes in the bile duct.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nakazawa et al considered biliary stricture limited to the intra-pancreatic area as IgG4-SC. 7,8 Naitoh et al reported that lower bile duct strictures appeared as marked wall thickening in 93% of patients, and as extrinsic compression in 7% of patients, revealing lower bile duct stricture caused mostly by bile duct wall thickening. 12 Other 14 studies also support that lower bile duct stricture in AIP is due to inflammatory processes in the bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…6 Sclerosing cholangitis is a major member of the disease group and is now recognized as IgG4-related sclerosing cholangitis (IgG4-SC) due to the infiltration of IgG4-positive plasma cells observed histologically within and around bile ducts, as well as in the pancreas. 7 IgG4-SC has been classified based on cholangiographic findings of duct stricture. 7,8 According to Nakazawa's classification, stricture in the lower part of the common bile duct is only classified as type 1, stricture diffusely distributed in the intrahepatic and extrahepatic bile duct as type 2, stricture distributed in both the hilar hepatic region and lower part of the common bile duct as type 3, and stricture in only the hilar hepatic region of the bile duct as type 4.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations